THE SPECIFICS OF DISCOURSE MODELING IN INTERCULTURAL COMMUNICATION - Malyugina, Nadezhda; Polyakova, Rauza; Fedorova, Elena; Tretyak, Elena; Shadskaja, Irina (Revista Inclusiones, 2020)
The study is devoted to the analysis of the specifics of discourse modeling in intercultural communication. It has been established that the features of the nomination of the main elements of a communicative event depend on the type of discourse that manifests itself in the specifics of the nomination of factors of the subject, chronotopos, cause and effect conditions of the event of intercultural communication. It has been proved that the complication of the type of discourse in intercultural communication leads to a decrease in specific concepts and an increase in the abstract definitions of each of the identified event factors through the use of means of expressing the subject’s formal social and interpersonal status. It has been determined that the cognitive effort in the formation of intercultural communication is a shift from interpersonal identity to social, from the everyday locally-centered stereotype towards the temporality of professional activity, increasing the abstractness of localization and time. It has been revealed that the proposed approaches to discourse modeling in intercultural communication help to find more complex patterns in the dependence on types of situations, typologies of subjects, stages of intercultural conflicts, and historicism of intercultural communication and to systematize aspects of the analysis of the discourse of intercultural communication.